Weight loss in children undergoing allogeneic hematopoietic stem cell transplantation within the first 100 days: Its influencing factors and impact on clinical outcomes - Yan, Mei; Pan, Jian; Huang, Jie; Liu, Changwei; Xia, Xiaona; Zhu, Ting; Wan, Yuanyuan; Fang, Yongjun; Tang, Weibing (Frontiers in Nutrition, 2023)
Purpose/objective: This study aimed to evaluate the nutritional status of children subjected to allogeneic hematopoietic stem cell transplantation (alloHSCT) in the first 100 days. Objectives were to clarify the effect of weight loss on clinical outcomes, and to analyze factors influencing weight loss. Methods: Eighty pediatric patients receiving alloHSCT were enrolled in the study. Body mass index (BMI) z-scores and weight for age (WFA) z-scores were collected. A multivariate regression model was set up to investigate factors affecting weight loss. Post-transplant clinical outcomes relative to weight loss on 100 days after transplantation were analyzed. Results: At admission, eight patients (10%) were underweight, the number had increased to 23 (30.67%) by 100 days post-HSCT. On day +100, only Nutrition screening tool for childhood cancer (SCAN) scores ≥3 (OR: 4.474, 95% CI: 1.215, 16.472; P=.024) and acute graft versus host disease (GVHD) (OR: 9.915, 95% CI: 3.302, 29.771; P<.001) were regarded as significant influencing factors of weight loss. The Weight loss ≥5% group was associated with longer hospital stays (P=.001), greater cost of inpatient treatment (P=.001), and a higher incidence of 100-day re-admission and intensive care unit (ICU) transfer (P=.03 and P=.033, respectively). Cumulative number of fever days (P=.023) and antibiotic use (P=.007) also increased significantly. The Weight loss ≥5% group had a significantly lower overall survival rate compared with the Weight loss <5% group (P=.015).